DNA i ruggfjädrar visar tajgasädgåsens Anser f. fabalisortstrohet till ruggningslokaler i Lappland - De Jong, Adriaan (2024)
Recently, the Taiga Bean Goose Anser f. fabalis breeding population of Southern Lapland, Sweden, was shown to use a network of local sites during their summer wing moult. We used microsatellite markers to identify individual geese from DNA in shed feathers collected in 2016–2020 on six sites, enabling us to identify 168 unique individuals from 178 fully genotyped feathers. Nine individuals were represented multiple times among the collected feathers. All controls of identified individuals were made on the original site, never on an alternative site. Our results suggest a significant level of site fidelity and, thus, the need to provide a stable, low-disturbance network of moulting sites for the Southern Lapland sub-population of this endangered taxon.